2021
DOI: 10.3389/fmicb.2021.705681
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metagenomics Reveals Microbial Communities and Their Associated Functions in Two Types of Fuzhuan Brick Tea

Abstract: Fuzhuan brick tea (FBT) is a unique post-fermented tea product, naturally co-fermented by microorganisms, and has gained global popularity due to its potential health benefits for humans. Considerable efforts have been made toward elucidating the microbial diversity within FBT, but an understanding of the underlying FBT community interactions and functions remains poorly studied. Consequently, the microbial communities of two types of FBT, originating from Hunan and Shaanxi provinces, were investigated using c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 52 publications
(53 reference statements)
2
9
0
Order By: Relevance
“…Moreover, a recent study has found that Bacillus correlated with 44 metabolites of Fu Brick tea, highlighting the importance of Bacillus in manufacturing Fu Brick tea (Xia et al, 2022 ). Although Pseudomonas were not significantly changed between different manufacturing stages in our study, they were revealed by metagenomic methods as the most important bacteria associated with 35 probiotics in Fu Brick tea (Wang et al, 2021 ). Other dominant bacteria, such as Paenibacillus , were reported to be one of the key microbes in the manufacture of other traditionally fermented foods, including Pu'er tea (Oh et al, 2008 ; Kim et al, 2009 ; Zhao et al, 2015 ).…”
Section: Discussionmentioning
confidence: 50%
“…Moreover, a recent study has found that Bacillus correlated with 44 metabolites of Fu Brick tea, highlighting the importance of Bacillus in manufacturing Fu Brick tea (Xia et al, 2022 ). Although Pseudomonas were not significantly changed between different manufacturing stages in our study, they were revealed by metagenomic methods as the most important bacteria associated with 35 probiotics in Fu Brick tea (Wang et al, 2021 ). Other dominant bacteria, such as Paenibacillus , were reported to be one of the key microbes in the manufacture of other traditionally fermented foods, including Pu'er tea (Oh et al, 2008 ; Kim et al, 2009 ; Zhao et al, 2015 ).…”
Section: Discussionmentioning
confidence: 50%
“…Moreover, the genera Sphingomonas, Chryseobacterium, and Aureimonas have been correlated with kaempferol, theaflavins, thearubigins, and theabrownins. Although there are few studies on the biotransformation of tea quality components by endophytic bacteria, some research has suggested that microorganisms secrete polyphenol oxidase and peroxidase during fermentation to promote the biotransformation of tea components [32], which forms the basis for the formation of black tea quality, flavor, and physiological functions. Additionally, there have been preliminary explorations of the biotransformation of tea polyphenols, such as a study that found the use of fungal-derived laccase and fresh tea-derived polyphenol oxidase can catalyze the conversion of catechins into complex polyphenolic compounds [33].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to polysaccharides, FBT is also rich in small molecule secondary metabolites, mainly including flavane‐3‐alcohols, noisoprene, acylated flavonoid glycosides, and triterpenes. Some compounds show good biological activity (Chen, Li, et al., 2021 ; Kong et al., 2019 ; Lu et al., 2019 ; Park et al., 2022 ; Wang, Du, et al., 2021 ; Zhou et al., 2022 ).…”
Section: Small Molecule Compounds and Their Activitiesmentioning
confidence: 99%